OTENTISITAS FILSAFAT ISLAM (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
Islamic philosophy is one of the fields of study whose existence has given rise to many pros and cons. Viewed from the point of view of the western intellectual tradition, islamic philosophy appears to be merely a Greco-Alexandrian philosophy in arabic 'clothes', a philosophy whose sole role is to channel certain important elements of ancient heritage to the Medieval West. The discussion of Islamic philosophy as a science must certainly refer to the existence of Islam itself with authentic sources that are derived from where a science originated and can develop and survive to the present day but in its course Islamic philosophy has received a lot of criticism from orientalists that Islamic Islamic philosophy does not exist and partly only a reduction from greek philosophical thought translated into arabic. And this also raises a big question for the author where the author got the question in 2020 during a comprehensive exam on islamic philosophy courses that the author still could not answer at that time. However, with the anxiety that is accused of Islamic philosophy the author describes in this paper. using the Library resech with the method of documentation studies finally the author finds the finding that Islamic philosophy is not true what is alleged by orintalism. From this paper, the author wants to see more about the authenticity of Islamic philosophy as a science in terms of terminology, sources, and figures of Islamic thought and how the roots of Islamic philosophy can be formed and survive, in the criticism of orientalism. Keywords, authenticity, urgensi, Islamic philosophy.